2003
DOI: 10.1121/1.1603765
|View full text |Cite
|
Sign up to set email alerts
|

Binaural sensitivity as a function of interaural electrode position with a bilateral cochlear implant user

Abstract: Experiments were conducted with a single, bilateral cochlear implant user to examine interaural level and time-delay cues that putatively underlie the design and efficacy of bilateral implant systems. The subject's two implants were of different types but custom equipment allowed presentation of controlled bilateral stimuli, particularly those with specified interaural time difference (ITD) and interaural level difference (ILD) cues. A lateralization task was used to measure the effect of these cues on the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 18 publications
(8 reference statements)
11
134
1
Order By: Relevance
“…This is comparable to the best thresholds found in our previous studies with single and 3-channel stimuli (Francart et al 2009. The thresholds are also comparable to thresholds found for the best bilateral CI listeners with single-channel stimuli (Laback et al 2007(Laback et al , 2004Lawson et al 1998;Litovsky et al 2010Litovsky et al , 2012Long et al 2003;Majdak et al 2006;Senn et al 2005;van Hoesel 2004van Hoesel , 2007van Hoesel and Tyler 2003). That sensitivity with multiple-channel stimuli is comparable to performance with single-channel stimuli is unlike performance often reported for NH listeners, for whom sensitivity increases with increasing bandwidth.…”
Section: Discussionsupporting
confidence: 87%
“…This is comparable to the best thresholds found in our previous studies with single and 3-channel stimuli (Francart et al 2009. The thresholds are also comparable to thresholds found for the best bilateral CI listeners with single-channel stimuli (Laback et al 2007(Laback et al , 2004Lawson et al 1998;Litovsky et al 2010Litovsky et al , 2012Long et al 2003;Majdak et al 2006;Senn et al 2005;van Hoesel 2004van Hoesel , 2007van Hoesel and Tyler 2003). That sensitivity with multiple-channel stimuli is comparable to performance with single-channel stimuli is unlike performance often reported for NH listeners, for whom sensitivity increases with increasing bandwidth.…”
Section: Discussionsupporting
confidence: 87%
“…When pulse presentation rates were increased to 200 pps, ITD thresholds were higher (~200碌s) (van Hoesel and Tyler 2003). Others have likewise reported that ITD thresholds increase with increases in stimulus rates (Laback et al 2004;Long et al 2003;Van Hoesel et al 2002;van Hoesel 2004;van Hoesel and Clark 1997). Our group has shown that auditory brain stem response amplitudes in children using cochlear implants deteriorate as the rate of electrical pulse rates increases (Davids et al 2008).…”
Section: Adult Bilateral Cochlear Implant Usersmentioning
confidence: 99%
“…Despite decreased sensitivities to ITD cues, some studies (Long et al 2003;Van Hoesel et al 2002;van Hoesel 2004;van Hoesel and Tyler 2003) have nonetheless indicated that adults with bilateral cochlear implants can perceive differences in time and especially intensity between devices. This suggests that some degree of binaural processing is available to adult bilateral cochlear implant users.…”
Section: Adult Bilateral Cochlear Implant Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitch-matched pairs of electrodes were tested in these experiments, which often maximize sensitivity to binaural cues in CI listeners (Long et al, 2003;Poon et al, 2009;Kan et al, 2013). Thus interaural place-of-stimulation mismatch may have also reduced binaural sensitivity in the CI listeners if the pitch matches did not fully compensate for interaural frequency mismatch.…”
Section: B Comparisons To Nh Performancementioning
confidence: 99%